Journal of crime and justice: JC&J (Routledge, Taylor & Francis Group)
"The Journal of Crime & Ju﻿stice is the official publication of the Midwestern Criminal Justice Association. The journal is a triannual peer-reviewed journal featuring original scholarly work in the area of crime and criminal justice"